Assessing the outcome of orthognathic surgery by three-dimensional soft tissue analysis - Vittert, L; Katina, S; Ayoub, A; Khambay, B; Bowman, A W (International journal of oral and maxillofacial surgery, 2018)
Studies of orthognathic surgery often focus on pre-surgical versus post-surgical changes in facial shape. In contrast, this study provides an innovative comparison between post-surgical and control shape. Forty orthognathic surgery patients were included, who underwent three different types of surgical correction: Le Fort I maxillary advancement, bilateral sagittal split mandibular advancement, and bimaxillary advancement surgery. Control facial images were captured from volunteers from local communities in Glasgow, with patterns of age, sex, and ethnic background that matched those of the surgical patients. Facial models were fitted and Procrustes registration and principal components analysis used to allow quantitative analysis, including the comparison of group mean shape and mean asymmetry. The primary characteristic of the difference in shape was found to be residual mandibular prognathism in the group of female patients who underwent Le Fort I maxillary advancement. Individual cases were assessed against this type of shape difference, using a quantitative scale to aid clinical audit. Analysis of the combined surgical groups provided strong evidence that surgery reduces asymmetry in some parts of the face such as the upper lip region. No evidence was found that mean asymmetry in post-surgical patients is greater than that in controls.
Keywords: dospělí; Facial Asymmetry; Female; fotografování; orthognathic surgery; zobrazování trojrozměrné; Imaging, Three-Dimensional; Adult; ženské pohlaví; Outcome and Process Assessment, Health Care; lidé; anatomická značka; Anatomic Landmarks; facial shape; Photography; asymmetry; Male; Orthognathic Surgical Procedures; Principal Component Analysis; ortognátní chirurgické výkony; comparison with controls; analýza hlavních komponent; mužské pohlaví; asymetrie obličeje; výsledky a postupy - zhodnocení (zdravotní péče); Humans